Changes in HER-2 and Matrix Metalloproteinase-2 Expression in Bone Marrow Micrometastasis and Stromal Cells in Men with Prostate Cancer as a Result of Androgen Blockade - Murray, N. P.; Reyes, E.; Badinez, L.; Orellana, N.; Fuentealba, C.; Olivares, R.; Porcell, J.; Duenas, R. (Perspective of Recent Advances in Medical Research Vol. 1, 2022)
We describe an immunocytochemical analysis of the impact of androgen inhibition on HER-2 and matrix metalloproteinase-2 (MMP-2) expression in bone marrow micrometastases and the surrounding stromal cells in prostate cancer patients. Men with prostate cancer who underwent bone marrow biopsy procedures had touch preps taken during androgen suppression, before and after radical prostatectomy. Patients were defined as HER-2 positive or negative, MMP-2 negative or an MMP-2 pattern described as border or central and stromal MMP-2 defined as positive or negative. The expression of the biomarkers was compared before and after initial treatment, as well as during androgen blockade, in relation to serum PSA at the time of sample and length of androgen blockade. There were 191 males included, 35 before surgery and 43 after; there were no appreciable variations in HER-2 expression between groups, and neither MMP-2 central nor stromal expression was present. MMP-2 expression in both micrometastasis and stroma was found to be substantially related to HER-2 expression. MMP-2 expression at the micrometastasis barrier was not linked with HER-2 expression and occurred in the absence of androgen blockade. Androgen deprivation lowers serum PSA by eradicating HER-2 negative prostate cancer cells. Early selection of HER-2 positive cancer cells, on the other hand, leads to androgen independence and enhanced expression of MMP-2 activity in the micrometastasis. Increased MMP-2 activity in micrometastasis boosts MMP-2 expression in surrounding stromal cells, which may promote angiogenesis and tumour growth, resulting in macrometastatic androgen independent illness.